The prevention of multi-drug resistance in cancers through the application of nanotechnology-based targeted delivery systems for combination therapies involving traditional Chinese medicine - Salik Abdullah; Shreya Mukherjee; Shweta; Biplab Debnath (Elsevier, 2024)
Introduction: The most significant obstacle in addressing cancer is the development of multidrug resistance during chemotherapy. Cancer cells have the ability to endure numerous cycles of traditional chemotherapy drugs before ultimately developing resistance to the treatment. Combining drugs is a strategy used to address the problem of multidrug resistance. Persistent challenges with synthetic drugs include catastrophic adverse reactions and other consequences. Natural compounds originating from traditional Chinese medicine are acknowledged for their minimal toxicity and possible benefits in reversing multidrug resistance induced by mainstream chemotherapeutic or targeted treatments. Cancer multidrug resistance (MDR) is an immediate clinical justification for unsatisfactory chemotherapy treatment. Cancer recurrence and metastasis are precipitated by MDR, leading to a high risk of death. The development of a unique nano-delivery method for the therapeutic management of MDR cancers has emerged as a key use of nanotechnology. Because of its significant anticancer prospective, traditional Chinese medicine (TCM)-combination therapy is an emerging treatment modality and an essential treatment option for cancer. By precisely regulating the release of medicines and delivering pharmaceuticals to cancerous cells, nano targeted drug-delivery devices offer amazing benefits and pave the way for the growth of TCM-combination therapies. Method: The present review examines the literature on three important topics: the mechanism of MDR in cancer chemotherapy, the role of traditional Chinese herbs and formulation in MDR treatment, and the incorporation of TCM in nanotechnology-based drug delivery systems to circumvent the limitations of traditional system. Major sources for the work include PubMed, Google Scholar, ResearchGate, Embase, and ScienceDirect. All the aspects pertaining to MDR, TCM, and nanotechnology for more than 50 years were considered, with an emphasis on the use of TCM in nano formulation, various forms of nano formulation, advances in the drug delivery system as a result of nanotechnology, and everything else in between. Results: As nanotechnology becomes more closely associated with TCM, the realm of practice for TCM is broadening. Furthermore, it enhances the prospects for future research and facilitates the advancement of modern Traditional Chinese Medicine (TCM). By integrating nanotechnology into a meticulously designed drug delivery system, TCM will enhance its ability to both treat and prevent diseases with even greater efficacy than previously. Discussion: This article examines nano-TCM and explores its characteristics, compositions, and relevant techniques for preparation and application in reversing MDR. In addition, a comprehensive elucidation of the key benefits of nano-TCM had been given with respect to MDR. The objective of this study was to analyze the existing body of literature on the application of nanotechnology in traditional Chinese medicine (TCM) that can be used in the treatment of MDR. The review encompasses various aspects like the development of active components for TCM, the utilization of TCM for reversing multidrug resistance (MDR), and the potential future advancements and obstacles associated with TCM-based nano combinations.